GENETIC AND HEMATOLOGICAL PROFILES OF Β-THALASSEMIAS IN EASTERN ALGERIA (Sciences & Technologie. C, Biotechnologies, 2016)
The present work is a retrospective cross-sectional study of cases of β-thalassemia in the Pediatric Department of the Constantine Regional Military Hospital (HMRUC) over a period of 3 months. Our objective is to study through these patients, on the one hand, the epidemiological and para-clinical aspects of β-thalassemia, and on the other hand, a genetic study by searching by RFLP-PCR for possible associations between T3801C polymorphisms of the gene CYP1A1 and C677T of the MTHFR gene and β-thalassemia. We collected during this period 36 cases of β-thalassemias aged between 3 months and 10 years with an average of 1.9 years and a sex ratio (M/F) of 2.25. The parents are consanguineous in 55,56% of the cases. The blood count was marked by pseudo-polycythemia and hypochromic microcytic anemia in thalassemic trait carriers and a decrease in red blood cell count and severe microcytic anemia in patients with severe forms. Hemoglobin electrophoresis revealed heterozygous β-thalassemia in 11 cases (30.55%) and homozygous β-thalassemia in 25 cases (69.44%). Statistical analysis of the preliminary results of molecular genotyping, represented by Odds ratio and the p-value, indicates the absence of association between the polymorphisms, C677T of MTHFR and T3801C of CYP1A1 and β-thalassemia. However, the size of the sample does not make it possible to invalidate or to confirm with certainty the presence or absence of this association.